A socio-technical approach to safety - Bredewold, M. (My University, 2014)
The requirement for commercial operations to implement safety management systems (SMS) coming into force, comes in a time where our approach and understanding of safety are changing. Even though traditional assumptions are much in common place, the regulator has adopted and mandated a seemingly straight-forward tool, which is, however, based on new, often not well explained or understood, and even conflicting philosophies and assumptions. Organisations and front-line workers find themselves in a dilemma, often faced with conflicting manifestations in a time where helicopter safety is already under much scrunity from a variety of stakeholders. In this paper we have a closer look at the implications of our history and the new requirements of safety management and its consequences in present times at operational level. Based on lessons learned, feedback, literature and observations, it is proposed to take into account and appreciate the valuable contribution of professional people in day-to-day operations, to maintain and improve our standard of operation with an increased focus on safety and (their) well-being.